If (p)=xsquare+3x+1 then find p(0) p(-1)

Question

If (p)=xsquare+3x+1 then find p(0) p(-1)

in progress 0
Melanie 1 month 2021-08-20T20:02:39+00:00 2 Answers 0 views 0

Answers ( )

    0
    2021-08-20T20:04:22+00:00

    Step-by-step explanation:

    p(x)=x^2+3x+1

    p(0)=(0)^2+3(0)+1

    p(0)=0+0+1

    p(0)=1

    p(x)=x^2+3x+1

    p(-1)=(-1)^2+3(-1)+1

    p(-1)=1-3+1

    p(-1)= -1

    p(0)×p(-1)=1× -1= -1

    0
    2021-08-20T20:04:27+00:00

    Step-by-step explanation:

    p(x) =  {x}^{2}  + 3x + 1 \\   p(0) =  {0}^{2}  + 3(0) + 1 = 0 + 0 + 1 = 1 \\ p( - 1) =  { (- 1)}^{2}   + 3( - 1) + 1 = 1 - 3 + 1 =  - 1

Leave an answer

Browse
Browse

18:9+8+9*3-7:3-1*13 = ? ( )